2008
DOI: 10.1055/s-0028-1083083
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Considerations in Revision Rhinoplasty

Abstract: Revision rhinoplasty is a unique challenge. In addition to the technical considerations that are inherently more difficult than those of primary cases, the surgeon must also be mindful of the psychological considerations that revision rhinoplasty presents. These patients are by definition unhappy with their prior rhinoplasty experience, and this perception of a suboptimal result is both legitimate and real, even if the surgeon is not in agreement. Tantamount to any intraoperative technique, the preoperative ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…These common but negative perceptions naturally contribute to a surgeon's discomfort and reluctance in dealing with these patients. [6][7][8] A recent study by Constantian challenged the stereotype of the secondary rhinoplasty patient. He looked at the motivations, outcomes, and prevalence of unfavorable results in 150 secondary rhinoplasty patients and found that most secondary rhinoplasty patients have a legitimate source of displeasure, and satisfaction was often achieved once the deformity was corrected.…”
Section: Discussionmentioning
confidence: 97%
“…These common but negative perceptions naturally contribute to a surgeon's discomfort and reluctance in dealing with these patients. [6][7][8] A recent study by Constantian challenged the stereotype of the secondary rhinoplasty patient. He looked at the motivations, outcomes, and prevalence of unfavorable results in 150 secondary rhinoplasty patients and found that most secondary rhinoplasty patients have a legitimate source of displeasure, and satisfaction was often achieved once the deformity was corrected.…”
Section: Discussionmentioning
confidence: 97%
“…Ambro et al reported these patients are unhappy with their prior rhinoplasty experience, and that the perception of a suboptimal result is both legitimate and real, even if the surgeon is not in agreement. Tantamount to any intraoperative technique, the preoperative ability of the surgeon to sift through the myriad of psychological and psychosocial issues is critical to achieving satisfactory outcomes for both the patient and surgeon 3 . In a previous study from our group, all patients undergoing rhinoplasty had a personality trait abnormality; the satisfaction rate of rhinoplasty was 55.1% 4 .…”
Section: Introductionmentioning
confidence: 91%
“…Personality disorders are some of the most commonly encountered psychological disturbance in patients seeking cosmetic surgery. 11,12 This is especially true in men seeking rhinoplasty who demonstrate a propensity for dominant, manipulative, egocentric, and emotionally labile behavior. Often these male personality traits can be summarized with the pneumonic "SIMON": single, immature, male, overly expectant, and narcissistic.…”
Section: Personality Disordersmentioning
confidence: 99%